Labor Productivity, Demographic Traits and ICT A Demo-Tech Productivity Model for Asian Region - Mehmood, Bilal; Azim, Parvez; Raza, Syed Hassan; Sohaib, Huma (International Journal of Economics and Financial Issues, 2014)
This paper develops an innovative model to explain the labor productivity in Asian countries, most of which are labor surplus and are endowed with substantial human capital. Such encouraging demographic traits are considered as complementary factors to use of Information and Communication Technologies (ICT). Population with labor having such favorable demographic traits and access to ICT results in higher labor productivity. Such is, here, termed as Demo-Tech Productivity Model and is tested by using data for 2000-2012 of 24 Asian countries. Econometric concerns like presence of endogenous and/or predetermined covariates and small time-series and cross-sectional dimensions of panel datasets are tackled by using System Generalized Method of Moments (SYS-GMM). Results show considerable support for the Demo-Tech Productivity hypothesis. Need is to design such models that suit the local demography and patterns of technological diffusion currently taking place in developing countries. Keywords: Labor Productivity; Information and Communication Technology (ICT); System Generalized Method of Moments (SYS-GMM); Human Development Index (HDI). JEL Classifications: C33; J24; O15; O33.